Proyecto de pre factibilidad de la producción de quinua en la zona 3, de la parroquia Palmira, cantón Guamote, provincia del Chimborazo con fines de exportación al mercado de Francia - Caviedes Salvatierra, Julio César (2015)
Ecuador has an extensive and multiple agricultural wealth, in attention to that wealth that has been ignored for years, the current government has decided to support the initiatives of micro, small and medium farmers to put their land to produce, not only with a view to have a purely primary production, but also the medium and long term production initiatives are developed in order to create value-added products. In the case of quinoa grown in the highlands of Ecuador, the research raises a possibility that from the parroquia Palmira where the golden grain as it is also known quinoa, is grown. The idea is that an association of producers that will take advantage of the important economic, social and marketing momentum governmental administration is giving farmers in the area; not only local production but with a view to export to one of the foreign markets that mostly consume quinoa, France…………